The Effect of Information Disclosure on Donor Commitment: The Case of Waqf Institution - Mohamad Isa Abd Jalil; Sofri Yahya; Anwar Allah Pitchay (Asian Academy of Management Journal, 2023)
This is an extension of an earlier study that examined the relationship between information disclosure on donor commitment related to waqf institution. Data was obtained from a sample of 558 individuals in Malaysia who are a repeating cash donor to waqf. Partial least squares-structural equation modelling (PLS-SEM) test using SmartPLS was used for data analysis. The findings indicated that future information disclosure and waqif (the person who gives waqf) significantly influenced the latter’s commitment. Additionally, the waqf, or trust in English, plays a role as a mediator between future information disclosure and governance information disclosure to the waqif’s commitment. This theoretical contribution has a practical implication as well in that, it indicates to the waqf or trust to disclose their report to donors to ensure sustainable collection.